A mixed integer non-linear programming model for optimizing the collection methods of returned products - Lamsali, Hendrik (2012)
This paper studies the problem manufacturers facing to determine the collection methods for used product at the end of its life. Three collection methods that are practically applicable are studied namely pick-up, drop-off and mail return. This paper investigates the problem of assigning collection methods to collect returned products from customer zones that can maximize manufacturer's profit. A mixed integer non-linear programming model integrating the three collection methods is proposed to tackle the problem. The model is then tested using some problem instances and the results are promising. The potential and benefits of the proposed model are also highlighted.